Why the par value of share matters to investors - Tadeusz Dudycz; Bogumiła Brycz (International Journal of Financial Studies, 2021)
The purpose of the study is the analysis of the relationship between the par value (also known as nominal value or face value) and the parameters influencing a company's financing. Additionally, the utility of the par value as a manipulation tool for equity offerings is examined. The study is based on a sample of IPO firms which went public on the Warsaw Stock Exchange. The study finds that an excess supply of shares has a negative impact on their valuation. In contrast, decreasing the par value prompts perceptual biases among investors beneficial to the success of the issuance. Moreover, share capital is found to be a useful signaling tool to improve the company's position on the financial market.
Keywords: 330; face value; financing; IPO; nominal value; par value; share capital; share premium; share price psychology; signaling; WSE